Architectured Leaf‐Inspired Ni0.33Co0.66S2/Graphene Aerogels via 3D Printing for High‐Performance Energy Storage. (23rd October 2018) - Tang, Xingwei; Zhu, Chengling; Cheng, Dongdong; Zhou, Han; Liu, Xianghui; Xie, Peiwen; Zhao, Qibin; Zhang, Di; Fan, Tongxiang
Abstract: The construction of high‐performance electrodes with sufficient active sites and interconnected networks for rapid electron/ions transport is challengeable for energy storage devices. Inspired by natural leaves, a facile 3D‐printing strategy for constructing architected Ni0.33 Co0.66 S2 /graphene (3DP‐NCS/G) aerogels to mimic the analogous mass transfer process toward superior electrochemical performances is demonstrated. The key step is to develop hybrid inks with printability and homogeneity by introducing sodium alginate into graphene oxide solutions to boost viscoelastic responses and adopting a new developed precursor Ni0.33 Co0.66 (OH)2 · x H2 O with ultrafine and high stable features. Benefiting from high‐speed channels for electron/ion transport provided by the interconnected graphene frameworks and massive exposed edge sites provided by the uniformly dispersed Ni0.33 Co0.66 S2 nanoparticles, the 3DP‐NCS/G electrode exhibits capacities of 217.6 mAh g −1 at 1 A g −1 and 164.6 mAh g −1 at 10 A g −1 . Furthermore, a hybrid device is demonstrated for the first time with both electrodes manufactured by 3D‐printing technique, which delivers excellent areal energy/power densities with values comparable to those of commercial devices, even at a practical level of electrode mass loading (17.86 mg cm −2 ). This work offers a versatile strategy for integrating various functional nanomaterials with programmable architectures toward myriad applications. Abstract : A shape‐programmable Ni0.33 Co0.66 S2 /graphene aerogel is 3D printed (3DP‐NCS/G) to mimic the mass transfer process of natural leaves . A hybrid ink is developed for components regulation and shape design. The interconnected networks and massive exposed edge sites of the 3DP‐NCS/G aerogels contribute to enhanced electrochemical performances. The device delivers competitive areal energy/power densities at practical levels of mass loading.